Capability of Asymmetrical Flow Field-Flow Fractionation (AsFlFFF) for Separation and Characterization of SiO2 Nanoparticles - Tae Kim, Sun; Chang Jung, Euo; Cho, Hye-Ryun; Park, Mi-Ri; Lee, Seungho (Asian Journal of Chemistry, 2012)
Asymmetrical flow field-flow fractionation (AsFlFFF) provides information on the size distributions of colloidal nanoparticles. Asymmetrical flow field-flow fractionation was employed to determine the size and size distribution of SiO2 nanoparticle samples having the nominal mean sizes of 20, 60 and 238 nm. Asymmetrical flow field-flow fractionation results showed the samples have size distributions broader than those provided by the particle manufacture. The same SiO2 nanoparticles were also analyzed by transmission electron microscopy (TEM) and dynamic light scattering (DLS) and the results were compared with those from AsFlFFF. Transmission electron microscopy images clearly showed the presence of aggregated particles, which seems to be the main reason why the size distributions obtained by AsFlFFF were broader. Results suggest that, particularly for particle samples having broad size distributions, AsFlFFF seems to provide a useful tool for size characterization.